Corporate Governance: Search for the Advanced Practices 2019
DOI: 10.22495/cpr19p14
|View full text |Cite
|
Sign up to set email alerts
|

The association between board diversity, earnings management and firm performance in Kuwait: A research agenda

Abstract: This paper aims to examine the consequences of board diversity. The objectives are to measure the impact of gender, age, national diversity on earnings management (EM). This research study raises the following questions: Does board diversity affect earnings management and firm performance? Has the 2013 Kuwait Corporate Governance Code impacted on board diversity on earnings management, beside firm performance? The research uses data from 103 non-financial Kuwaiti listed companies in the period from 2010 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 66 publications
3
14
0
6
Order By: Relevance
“…Our study results also show that women's presence on the board mitigates earnings management (β=-0.104419; p= 0.0024). This result is in agreement with those of Alqatan (2019), Debnath and Roy (2019), Kyaw et al (2015), Mnif andCherif (2020), andTriki Damak (2018). Indeed, women on the board of directors are more motivated.…”
Section: Main Results and Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Our study results also show that women's presence on the board mitigates earnings management (β=-0.104419; p= 0.0024). This result is in agreement with those of Alqatan (2019), Debnath and Roy (2019), Kyaw et al (2015), Mnif andCherif (2020), andTriki Damak (2018). Indeed, women on the board of directors are more motivated.…”
Section: Main Results and Findingssupporting
confidence: 90%
“…Previous research papers have studied this factor using the number or percentage of female directors actively operating within the governance body by examining the relationship between their presence within the board composition and earnings management (Alqatan, 2019;Debnath and Roy, 2019;Kyaw et al 2015;Mnif and Cherif, 2020;Triki Damak, 2018). These researchers showed that earnings manipulation is lower in companies with higher female board representation.…”
Section: Gender Diversitymentioning
confidence: 99%
“…Gender diversity on a board is viewed as being good corporate governance (Gallego-Alvarez et al, 2010;Alqatan, 2019). This is mainly argued due to: (1) the addition of unique characteristics, abilities and talent to the board; (2) the enhancement of the problem-solving skills of a board, and the possibility of looking at problems from different perspectives, which provides alternative solutions and enhances firm performance (Rose, 2007).…”
Section: Board Diversity and Firm Performancementioning
confidence: 99%
“…Hasil penelitian yang membahas pengaruh usia dewan direksi terhadap manajemen laba telah dilakukan oleh Alqatan (2019) yang menemukan bahwa usia direksi berpengaruh positif terhadap manajemen laba pada perusahaan yang go public di Indonesia. Hasil yang penelitian yang berbeda ditemukan oleh Zwet, (2017) serta hasil penelitian Govindan et al (2021), yang menemukan bahwa usia yang dimiliki dewan direksi berpengaruh negatif terhadap kegiatan manajemen laba.…”
Section: Pendahuluanunclassified
“…Usia dapat mempengaruhi kinerja seorang dalam perusahaan yang kemudian dapat mempengaruhi nilai perusahaan dalam membuat laporan keuangan. Alqatan (2019) mengungkapkan usia dewan direksi akan mendorong anggota dewan direksi muda atau pun tua untuk saling bertukar fikiran sebelum mengambil sejumlah keputusan strategis untuk kemajuan perusahaan. usia akan menciptakan sinergi yang kuat antara anggota dewan direksi muda atau pun tua untuk melakukan sejumlah tindakan untuk menyelamatkan reputasi perusahaan termasuk kecenderungan dewan direksi untuk mendukung tindakan manajemen laba yang dilakukan manajer.…”
Section: Literatur Review Dan Hipotesisunclassified